Transforming food systems under a changing climate in Latin America: A climate policy review - Martínez Barón, Deissy; Castellanos, Andrea; Gonzalez Rodriguez, Carlos Eduardo; Le Coq, Jean-François (2019)
Agriculture is highly vulnerable to climate change, but at the same time, it is the main contributor to climate change Governments have recognized that facing climate change is essential to address a sustainable development pathway, but so far little progress has been achieved Thus there is a need for rapid and transformative actions that tackle climate change impacts while achieving sustainable rural development Nevertheless, the way current policies are addressing actions towards transformative actions is unclear concerning sustainable pathways of food systems in the face of climate change.